2016
DOI: 10.1590/1981-5344/2537
|View full text |Cite
|
Sign up to set email alerts
|

A Co-authorship network analysis of CNPq’s productivity research fellows in the probability and statistic area

Abstract: In this paper, we analyzed the co-authorship network between all CNPq’s productivity research fellows in the Probability and Statistics area in Brazil. Our aim was to describe and to understand how network measures influence researchers’ productivity. The data was gathered from the CNPq’s Lattes Platform using the software scriptLattes, and a link between two fellows represents the fact that they wrote an article together from 2009 to 2013. The network is disconnected and has only 4.7% of its possible connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Cimenler et al [16] collected collaborative output data of researchers in a self-reporting way, which can provide some instructions on whether collaborative research is important or not, and improved the authenticity and accuracy of the results to a certain extent. More specifically, Souza et al [17] used a co-author network to assess the mechanisms of human interaction and productivity performance in specific groups with changes in various network indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Cimenler et al [16] collected collaborative output data of researchers in a self-reporting way, which can provide some instructions on whether collaborative research is important or not, and improved the authenticity and accuracy of the results to a certain extent. More specifically, Souza et al [17] used a co-author network to assess the mechanisms of human interaction and productivity performance in specific groups with changes in various network indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The authority also showed significant, but negative correlation. Souza et al (2016), in a co-authorship network among researchers with CNPq grant in research productivity in the area of Statistics, showed that the most productive fellows are also the most central in the network and that the metrics degree centrality and closeness centrality had a higher impact on the number of articles published by a fellow.…”
Section: Introductionmentioning
confidence: 99%